EP536 Obesity and gynaecological oncology surgery in Wales: rising to the challenge of an expanding population. (1st November 2019) - Haken, A; Sharma, A; Lim, K; Howells, R
Abstract : Introduction/Background: Obesity in the UK is a growing problem and is classically associated with increasing comorbidities, longer operative time and more complications. It is increasingly common for gynaecological surgeons to operate laparoscopically which has proven benefits of reducing complications such as wound dehiscence and infection, and shortens recovery time. However there are additional challenges with laparoscopy in these patients including a need for longer instruments, technically difficult access, and restrictions in positioning and insufflation pressures used for surgery. Methodology: The aims were to determine the number of laparoscopic hysterectomies performed for cancer in University Hospital of Wales over last 5 years, and analyse complication rates in relation to body mass index (BMI). Retrospective data analysed on laparoscopic gynaecological oncology surgery from the last 5 years. Data was used to assess operation type in association with BMI and complication rates, conversion to open procedure rates, intra-operative blood loss and length of stay. Results: The Gynae-Oncology service at the University Hospital of Wales has performed 589 laparoscopic hysterectomies since 2015, and over 80% of these in overweight or obese women. This data demonstrates an increasing trend of overweight and obese patients over the last 5 years, and yet no significant increase in complication rates or length of stay. The overall complication rate was 5.1%, and conversion to open procedure was required in 2%. Conclusion: The findings suggest that surgical skill has developed in line with the additional challenges of obese patients in gynaecological oncology surgery, enabling a quicker recovery and a smoother return to normal life. Disclosure: Nothing to disclose.